The effect of overall service quality on customer satisfaction: The moderating role of travel experience - Gu, Shengyu (Turyzm/Tourism, 2023)
The purpose of this study is to explore the relationship between overall service quality and customer satisfaction, further, this relationship is examined in terms of travel experience as a moderator. The study mainly focuses on eco-tourism and collected data from tourists travelling to China. Convenience sampling was used for data collection and a questionnaire used from previous studies. AMOS software analyzed the data collected from 341 respondents. The results highlighted that there is a significant and positive relationship between overall service quality and customer satisfaction. Moreover, the presence of travel experience as a moderator strengthens this relationship. This research is limited to eco-tourism and future studies could be done from the perspective of any other country with a large sample size.